2021
DOI: 10.1002/ejp.1755
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of new‐onset pain in COVID‐19 survivours, a controlled study

Abstract: We assessed whether COVID‐19 is associated with de novo pain and de novo chronic pain (CP). This controlled cross‐sectional study was based on phone interviews of patients discharged from hospital after COVID‐19 compared to control group composed of individuals hospitalized during the same period due to non‐COVID‐19 causes. Patients were classifyed as having previous CP based on the ICD‐11/IASP criteria, de novo pain (i.e., any new type of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
2
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 61 publications
11
73
2
8
Order By: Relevance
“…54,55 It can persist over the period of the initial infection, 56 or it can develop as a new-onset form during healing. 11 Proposed mechanisms include direct invasion of trigeminal nerve endings by SARS-CoV-2 via disruption of the brain-blood barrier, trigeminovascular activation via involvement of endothelial cells with ACE2 expression, or triggering of perivascular trigeminal nerve endings by release of cytokines and pro-inflammatory mediators. 56 Among other symptoms, almost half of the patients developed fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 It can persist over the period of the initial infection, 56 or it can develop as a new-onset form during healing. 11 Proposed mechanisms include direct invasion of trigeminal nerve endings by SARS-CoV-2 via disruption of the brain-blood barrier, trigeminovascular activation via involvement of endothelial cells with ACE2 expression, or triggering of perivascular trigeminal nerve endings by release of cytokines and pro-inflammatory mediators. 56 Among other symptoms, almost half of the patients developed fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the collected data on pain focused on headache and little is known about overall pain syndromes. A previous study by Soares et al ( 2021 ) reported that patients with COVID‐19 had a higher prevalence of de novo pain (65.2%) and de novo headache (39.1%) when compared with a control group and they found de novo chronic pain in 19.6% of patients with COVID‐19. Another study revealed pain in 69.3% of patients with COVID‐19 with 69.2% of those reporting myalgia/arthralgia, 50.4% headache, 43.6% back pain, and 33.1% reporting low back pain (Murat et al, 2020 ).…”
Section: Introductionmentioning
confidence: 90%
“…Another study revealed pain in 69.3% of patients with COVID‐19 with 69.2% of those reporting myalgia/arthralgia, 50.4% headache, 43.6% back pain, and 33.1% reporting low back pain (Murat et al, 2020 ). Although research has focused on individual pain syndromes, there is still a gap regarding the overall pain symptoms and characteristics, leaving many unresolved questions concerning the characteristics of pain in patients with COVID‐19 (Magdy et al, 2020 ; Murat et al, 2020 ; Soares et al, 2021 ; Uygun et al, 2020 ). Describing the characteristics of pain syndromes, which may result from different mechanisms, will help to better understand the different mechanisms of pain and will improve the choice of pain medication.…”
Section: Introductionmentioning
confidence: 99%
“…Soares и соавт. [37] сравнили наличие скелетномышечной боли у 46 пациентов, находившихся в стационаре для лечения COVID-19, и 73 лиц, госпитализированных в тот же период по другим причинам. После выписки из стационара частота хронической боли (продолжавшейся более 3 месяцев) у пациентов после COVID-19 составила 19,6%, в контрольной группе -1,4% (р=0,002).…”
Section: клинические проявления пкс: утомляемость и больunclassified